2016
DOI: 10.1186/s40064-016-3641-z
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy and duodenogastric reflux: interacting effects over the gastric mucosa

Abstract: AimsTo evaluate association between duodenogastric reflux and early gastric mucosal changes before and after the cholecystectomy procedure.Materials and methodsPatients were evaluated with preoperative and postoperative endoscopy and endoscopic biopsy. Demographic and clinical characteristics, histological parameters, presence of duodenogastric reflux, and Updated Sydney scores were noted.ResultsA total of fifty patients who obeyed the follow-up were enrolled into the study. Median age of the patients was 43 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
2
14
0
2
Order By: Relevance
“…Studies have reported that H. pylori gastritis is seen equally in both genders because of the same probability of being affected by H. pylori infection, but DGR may be more common in women due to functional pathophysiology [19]. Mercan et al reported that there was no significant gender difference between groups with and without DGR [22]. The results obtained from our study support this finding.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have reported that H. pylori gastritis is seen equally in both genders because of the same probability of being affected by H. pylori infection, but DGR may be more common in women due to functional pathophysiology [19]. Mercan et al reported that there was no significant gender difference between groups with and without DGR [22]. The results obtained from our study support this finding.…”
Section: Discussionsupporting
confidence: 87%
“… 25 Hyperglycemia can reduce gastric acid secretion by inhibiting the vagal cholinergic pathways, 7 , 8 and a recent previous study identified cholecystectomy as a cause of the severe duodenogastric reflux strongly associated with early gastric mucosal changes. 26 The high osmotic pressure induced by i.v. dextrose also can reduce gastrointestinal wall contractions.…”
Section: Discussionmentioning
confidence: 99%
“…13 En México en 2016 se realizó un estudio con 345 pacientes que padecían síndrome de colon irritable con el subtipo de predominancia de diarrea, en el cual se describió que la prevalencia de dicho síndrome en pacientes colecistectomizados fue 3.6 veces mayor. 27 Por otro lado, la incidencia de gastritis diagnosticada por endoscopia por dolor crónico postcolecistectomía también se ha descrito antes, 28 se considera a la colecistectomía como un riesgo significativo para la gastritis biliar, 29 causante de reflujo y cambios en la mucosa gástrica, 30 incluso se ha supuesto tratamiento con ácido ursodesoxicólico en el tratamiento para la gastritis por reflujo alcalino postcolecistectomía con efectos positivos. 31 De hecho, se ha sugerido que en pacientes que serán sometidos a una colecistectomía deba realizarse una endoscopia preoperatoria, ya que en 28.8% de los casos existen cambios endoscópicos que expliquen el dolor abdominal, 32 los diagnósticos más frecuentes causantes del síndrome postcolecistectomía son úlceras pépticas y hernias hiatales.…”
Section: Wwwmedigraphicorgmxunclassified